[C–H⋯anion] interactions mediate the templation and anion binding properties of topologically non-trivial metal–organic structures in aqueous solutions. Issue 4 (26th February 2016) - Bilbeisi, Rana A.; Prakasam, Thirumurugan; Lusi, Matteo; El Khoury, Roberto; Platas-Iglesias, Carlos; Charbonnière, Loïc J.; Olsen, John-Carl; Elhabiri, Mourad; Trabolsi, Ali
Abstract : We report the anion-recognition properties and anion-mediated templation of Metal-Organic knots and links in aqueous solutions. Abstract : Two synthetic approaches—temperature variation and anion templation—allowed for the selective formation of a [2]catenane ([2]C 4+ ) or a trefoil knot (TK 6+ ), or for the enhanced formation of a Solomon link (SL 8+ ), all from a simple set of starting materials (Zn(ii ) acetate, diformylpyridine (DFP) and a diamino-2, 2′-bipyridine (DAB)) in mixed aqueous solutions. The catenane formed exclusively at 90 °C in a 1 : 1 mixed solvent of D2 O and MeOD. In the presence of bromide ion as template, TK 6+ formed exclusively at 50 °C in the same solvent. In the solid state, TK 6+ hosts two bromide ions in its central cavity by forming six Csp 2 –H hydrogen bonds. In D2 O, TK 6+, which was originally prepared as a trifluoroacetate (TFA) salt, was found to exchange two TFA counterions for two monovalent anions of different sizes and shapes, which lodged within the knot's central cavity. In contrast to bromide, the larger triflate anion (CF3 SO3 − ) promoted the formation ofSL 8+, which was characterized by 1 H NMR spectroscopy and mass spectrometry. Two dimensional heteronuclear 19 F- 1 H-HOSEY NMR experiments detected CH⋯F interactions inside the cavity ofSL 8+ . Thus, the product distribution of this dynamic link forming system is sensitive to temperature and the size and shape of the anion template, and one of the products, TK 6+, is capable of binding a variety of monovalent anions in D2 O with high affinity (with log β 2 values of 4 to 6 being typical).